2015
DOI: 10.1515/ljss-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Speed Training on Sprint and Agility Performance in 15-Year-Old Female Soccer Players

Abstract: The main aim of this study was to investigate the effects of short burst speed and change-of -direction exercises on sprint and agility performance in youth female soccer players 15.5 (± 0.7) years. One training group (n=10) followed an eight-week, once per week training program consisting of short-burst sprinting exercises in addition to two normal soccer training, while a control group (n=9) followed three traditional soccer training session. Pre-and post-tests assessed significant improvement in 10 m sprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
1
27
0
1
Order By: Relevance
“…COD ability is one of the most important components in soccer [31]. Its improvement has become a focus of training programmes in adolescent female soccer players [32, 33]. However, trivial results (ES: -0.01 to 0.32) were found in the EG in all COD tests after the FIFA 11+ programme in this study.…”
Section: Discussionmentioning
confidence: 55%
“…COD ability is one of the most important components in soccer [31]. Its improvement has become a focus of training programmes in adolescent female soccer players [32, 33]. However, trivial results (ES: -0.01 to 0.32) were found in the EG in all COD tests after the FIFA 11+ programme in this study.…”
Section: Discussionmentioning
confidence: 55%
“…24 This is in line with previous reports of 10- to 12-year-old boys. 2 , 19 , 28 However, another study, with 12-year-old boys, found a significant correlation between the 50 m sprint and height. 29 …”
Section: Discussionmentioning
confidence: 89%
“…These results are supported by previous reports among young males aged 10–14 years. 19 , 20 , 28 Jones et al 34 suggest that, at early stages of athlete development, a basic improvement in sprint may lead to an improvement in agility performance. However, in the 15- to 16-year-olds, the correlation was weaker, with r -values from 0.37 to 0.47 ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Men, U-197/ 1–2Pre:8.67 ± 0.29 Post:8.74 ± 0.42NoneEG: 0.81%EG, ES = 0.198Small-sided game, 4vs4 and 2vs2. 30–45 sPlanned AFL-agility1) 8 m2) 13) 135 °Chaouachi et al [89]EG, n = 12CG, n = 12Age:14.2 ± 0.9Young Men, elite- Soccer6/3Pre: 7.40 ± 0.56Post:7.03 ± 0.47Pre:7.74 ± 0.32Post:7.54 ± 0.30EG: 2.47%CG: 2.58%EG, ES = 0.67CG, ES = 0.65Small sided game, 1vs1 (30 sec), 2vs2(1 min) and 3vs3(2 min)Zig-zag test1) 20 m2) 33) 100 °Resisted sprintsde Hoyo et al [77]EG, n = 12Age: 17 ± 1Men, Jr elite- level Soccer8/2Pre: 5.26 ± 0.16Post:5.28 ± 0.17NoneEG: -0.38%EG, ES = -0.12Resisted Sprint with 12,6% of athletes BM, 20 m sprint, S:1, R:4Zig-zag test4) 20 m5) 36) 100 °Prieske et al [72]EG, n = 10Age: 23 ± 3CG, n = 16Age: 23 ± 3Men and Women, University students6/3Pre:11.03 ± 1.23Post: 10.65 ± 0.58Pre:10.42 ± 0.91Post: 10.2 ± 0.86EG: 3.45%CG: 2.11%EG: ES = 0.42CG, ES = 0.25Resisted sprint exercises with elastic straps on motorized treadmill.S: 3–4 T test1) 40 m2) 43) 2 × 90 ° and 2 × 180 °Mathisen and Pettersen [97]EG, n = 10Age:15.5 ± 0.7CG, n = 9Age: 15.1 ± 0.5Young Women, Soccer8/1Pre:8.23 ± 0.31Post:7.80 ± 0.33Pre: 8.04 ± 0.14Post: 8.01 ± 0.15EG: 5,22%CG: 0,37%EG, ES = 1,34CG, ES = 0,21Resisted Sprint, over-speed run, sprint with change direction. Total 32 sprints, 15–20 mAgility course1) 20 m2) 43) 2 × 90 ° and 2 × 180 °Straight forward sprintYoung et al [98]EG, n = 13CG, n = 10Age: 24.0 ± 5.7Volunteer 1-year experience with COD6/2Pre: 9.51 ± 0.52Post: 9.51 ± 0.52Pre: 9.68 ± 0.67Post: 9.78 ± 0.66EG:0%CG:-1.03%EG, ES = 0CG, ES = -0.15Straight forward sprint, with varied distances (20 m – 40 m)1) 30 m2) 53) 100 °Repeated sprintChtara et al [51]EG, n = 12Age:13.6 ± 0.3CG, n = 10Men, Jr, Soccer7/1Pre:7.15 ± 0.20 Post:6.88 ± 0.14Pre:7.12 ± 0.22 Post:7.07 ± 0.21EG:3.78%CG:0.70%EG, ES = 1.59CG, ES = 0.23Repeated sprint with different distances and series, R:2, S:2–4Zig-zag test1) 20 m2) 33) 100 °Taylor et al [93]EG, n = 8Age: 24.1 ± 4.1Semi- prof. Men, Soccer2...…”
Section: Methodsmentioning
confidence: 99%